Review of the Legality of Binary Options According to Islamic Law and Laws in Indonesia - Irkham Firdaus, Muhammad; Hisyam Hawari, Muhammadudy; Fathin Nur Ihsan, Muhammad (Gayaku Publisher, 2022)
A binary Option is a financial or financial product in which the parties involved are placed on one of two options within a certain period of time. Juridically, the legality of Binary Options as a Futures Trading Commodity is still being debated. This is because in order to be considered a commodity, it must fulfill the phrase